Correlation analysis of differential genes in two different tissues of diabetic nephropathy patients - Jin-ming Zhang; Lian Zhang; Li-hua Ni; Hui-ling Feng; Xiao-yan Wu (Linchuang shenzangbing zazhi)
ObjectiveTo screen the differential genes of peripheral blood mononuclear cells （PBMCs） and glomerular tissue of diabetic nephropathy （DN） patients and identify potential biomarkers for diagnosing the disease and targeted gene therapy.MethodsThe PBMC RNA data of DN patients and normal subjects were extracted from GSE142153 in GEO database. Then glomerular RNA data of DN patients and normal subjects were extracted from GSE30528 chip. Then GEO2R tool of GEO and Excel were utilized for screen differential genes.ResultsThere were 201 differentially expressed genes in PBMC of DN patients and 845 differential genes in glomerular tissue. The differential genes of glomerular tissues were predominantly involved in renal systemic development. Differential genes of PBMC participated mostly in renal tissue inflammation in DN. EMP1， MAFB， GADD45A， ATF3， RASL11B， F3， CCR2， TLR7， EGF， TIPARP， P2RY14， CD24， IGKC and DACH1 genes were expressed differentially in two tissues at the same time. There was an interaction between TLR7， CCR2， CD24， EGF， ATF3， MAFB， GADD45A and F3 genes.ConclusionThe differential genes of PBMC and glomerulus vary in DN patients， as well as the mechanism of differential genes in DN. In DN patients， 16 genes are expressed differentially in two tissues at the same time so that they may be employed as a diagnostic biomarkers of DN. Based on the differences and correlations between the expressions of these 16 genes in PBMC and glomerulus， they shall facilitate non-invasive detection of DN. In addition， an interaction exists between 8 genes in PBMC and glomerulus so that there are potential therapeutic targets for DN.